Intraorganizational conditions for social innovation in sport for development and peace - Svensson, Per G.; Mahoney, Tara Q. (Managing leisure, 2020)
Research question: What are the intraorganizational conditions necessary for social innovation in Sport for Development and Peace (SDP)? Research methods: Data were collected via semi-structured interviews and focus groups from 51 leaders in the SDP field who received awards for their innovative work and/or had notable reputations as innovators in the SDP field. Findings: Findings highlight how an SDP organization's culture, leadership, paid staff, organizational infrastructure, and financial resources enable social innovation. Several sub-themes were identified as particularly important in the SDP context. Practical implications: A more detailed understanding of these internal conditions help identify ways funders and policymakers can better support the development of more creative and sustainable organizations able to successfully adapt to changing environments and social issues. Research contribution: This study provides a starting point for theoretical advancements on the intraorganizational conditions necessary for the development and implementation of social innovation in sport.